PAI sebagai Sarana Pendidikan Kebersihan dan Higiene untuk Membangun Kesadaran Lingkungan - Muhammad Ulil Azmi; Ihdi Ma'adi; Wahdatul Ummah (FKIP UNSULTRA, 2025)
Islamic Religious Education (PAI) plays a strategic role in shaping students' character, including in areas such as cleanliness, hygiene, and environmental awareness. The value of cleanliness is strongly emphasized in Islamic teachings, as reflected in the concepts of thaharah (purification), personal etiquette, and human responsibility as a caliph in preserving nature. This research aims to examine how PAI can be an effective means of instilling clean and environmentally conscious behaviors through a literature approach. The study compiled and analyzed various studies from national and international journals that discuss environmental education, PAI learning, and the integration of hygiene values ​​into religious learning. The findings indicate that PAI not only emphasizes physical cleanliness but also instills spiritual awareness about the relationship between humans, the environment, and God. The integration of hygiene materials into PAI has been shown to improve students' hygiene behaviors—from handwashing habits and maintaining school cleanliness to waste management. Furthermore, a pedagogical approach based on teacher role models, habituation, and environmental action projects has proven effective in fostering ecological awareness. This study confirms that PAI can be a powerful instrument in building awareness of cleanliness and hygiene when integrated systematically, contextually, and sustainably into learning practices.